Going through the Challenges of Artificial Intelligence: Gray Eminences, Algocracy, Automated Unconsciousness - Baldi, V. (What AI Can Do Strengths and Limitations of Artificial Intelligence, 2023)
In the sociotechnical condition that involves and challenges the balance of contemporary social life, new political protagonists and governance regimes emerge. Technological innovations that rely on AI systems accelerate the reconfiguration of the social structures of cultural and political intermediation, as well as of anthropological and cognitive dispositions in the face of changes in the digital environment. New influencers emerge in the public sphere, but also new influencers of influencers (the eminences grise in a computational version), and democracies acquire characteristics of algocracies. The decision-making processes that substantiate the life of institutions and governments suffer from the dilemma of how to justify decision-making in contexts based on the attribution of competence and intelligence to automatized systems. To deepen the understanding of these transformations, it is necessary to deconstruct the logic that underlies the design and operation of AI systems. Analyzing the ecology of the interconnected devices through which we interact with our environments, more or less familiar, we can trace a path of reappropriation and accountability of the functionalities of the devices that we can call “artificial unconsciousness”.